Serum interferon-α2 measured by single-molecule array associates with systemic disease manifestations in Sjögren's syndrome. (10th September 2021) - Huijser, Erika; Göpfert, Jens; Brkic, Zana; van Helden-Meeuwsen, Cornelia G; Jansen, Sanne; Mandl, Thomas; Olsson, Peter; Schrijver, Benjamin; Schreurs, Marco W J; van Daele, Paul L A; Dik, Willem A; Versnel, Marjan A
Abstract: Objectives: Type I IFN (IFN-I) activation is a prominent feature of primary SS (pSS), SLE and SSc. Ultrasensitive single-molecule array (Simoa) technology has facilitated the measurement of subfemtomolar concentrations of IFNs. Here we aimed to measure IFN-α2 in serum from pSS, SLE and SSc using a Simoa immunoassay and correlate these levels to blood IFN-stimulated gene (ISG) expression and disease activity. Methods: Serum IFN-α2 was measured in patients with pSS ( n  = 85 and n  = 110), SLE ( n  = 24) and SSc ( n  = 23) and healthy controls (HCs; n  = 68) using an IFN-α Simoa assay on an HD-X analyser. IFN-I pathway activation was additionally determined from serum by an IFN-I reporter assay and paired samples of whole blood ISG expression of IFI44, IFI44L, IFIT1, IFIT3 and MxA by RT-PCR or myxovirus resistance protein 1 (MxA) protein ELISA. Results: Serum IFN-α2 levels were elevated in pSS (median 61.3 fg/ml) compared with HCs (median ≤5 fg/ml, P  < 0.001) and SSc (median 11.6 fg/ml, P  = 0.043), lower compared with SLE (median 313.5 fg/ml, P  = 0.068) and positively correlated with blood ISG expression ( r  = 0.66–0.94, P  < 0.001). Comparable to MxA ELISA [area under the curve (AUC) 0.93], IFN-α2 measurement using Simoa identified pSS with high ISG expression (AUC 0.90) with 80–93% specificity and 71–84% sensitivity. Blinded validation in an independent pSS cohort yielded a comparable accuracy. Multiple regression indicated independent associations of autoantibodies, IgG, HCQ treatment, cutaneous disease and a history of extraglandular manifestations with serum IFN-α2 concentrations in pSS. Conclusion: Simoa serum IFN-α2 reflects blood ISG expression in pSS, SLE and SSc. In light of IFN-targeting treatments, Simoa could potentially be applied for patient stratification or retrospective analysis of historical cohorts.